Bridging the trade finance gap for export-oriented SMEs: A systematic literature review (International Journal of Business, Economics and Management, 2024)
Small and Medium Enterprises (SMEs) are the most efficient segment of all global economies. They often struggle to adjust to the constantly changing requests imposed by the dynamic international markets, especially those in developing countries. Inadequate access to trade finance is one of the main constraints faced by SMEs engaged in international trade exports. The aim of this paper is to explore the factors affecting access to trade finance by export-oriented SME and the remedial steps taken to bridge the trade finance gap in the Sri Lankan context as well as the global context. The research methodology employed is a comprehensive systematic review of literature. Based on the review of selected 64 articles, we find that banking sector weaknesses, internal weakness within the SMEs and the insufficiency of government support have an effect on the access to trade finance by the export oriented SMEs. In addition, a number of remedial measures in bridging the trade finance gap are also identified. This systematic literature review addresses the research gap existing due to the limited availability of literature on the same domain. The findings signal towards government policymakers and stake holders in revamping their initiatives towards bridging the global trade finance gap, successfully. And creates as an optimal foundation for future empirical research endeavors.